2020
DOI: 10.31219/osf.io/jvfds
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moral Decision-Making during COVID-19: Moral judgments, moralisation, and everyday behaviour

Abstract: The COVID-19 pandemic continues to pose significant health, economic, and social challenges. Given that many of these challenges have moral relevance, the present study investigates whether the COVID-19 pandemic is influencing moral decision-making and whether moralisation of behaviours specific to the crisis predict adherence to government-recommended behaviours. While proto-utilitarian tendencies and utilitarian moral judgments remain unchanged during the pandemic, individuals have moralised non-compliant be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…When both sides of the spectrum feel their particular preference is the morally correct course of action, the other party is not just 'different' but 'wrong' (Goodwin & Darley, 2012). As COVID-19 mitigating behaviours (such as social distancing or mask wearing) are so strongly seen as morally relevant practices (Francis & McNabb, 2020), their continued enactment as regulations ease means potentially walking on socially thin ice. Perceived moral motivation for behaviour, regardless of specific content of the moral arguments, is enough to produce defensiveness and self-concept threat in others, which may lead individuals to 'doubledown' on their own moralized behaviour and derogate others who behave differently (Cramwinckel, van Dijk, Scheepers & van den Bos, 2013).…”
mentioning
confidence: 99%
“…When both sides of the spectrum feel their particular preference is the morally correct course of action, the other party is not just 'different' but 'wrong' (Goodwin & Darley, 2012). As COVID-19 mitigating behaviours (such as social distancing or mask wearing) are so strongly seen as morally relevant practices (Francis & McNabb, 2020), their continued enactment as regulations ease means potentially walking on socially thin ice. Perceived moral motivation for behaviour, regardless of specific content of the moral arguments, is enough to produce defensiveness and self-concept threat in others, which may lead individuals to 'doubledown' on their own moralized behaviour and derogate others who behave differently (Cramwinckel, van Dijk, Scheepers & van den Bos, 2013).…”
mentioning
confidence: 99%
“…The aim of study 1 was to compare the moral decision-making, level of perceived stress, the ability of mentalizing, and empathy in front-line workers (FLW), second-line workers (SLW), and university students (US) during COVID-19 pandemic. As pointed out by Francis and McNabb (2020), moral judgment can be influenced by specific features of the situation and characteristics of decision-makers, such as mood.…”
Section: Studymentioning
confidence: 99%
“…During an emergency like a pandemic, some decisions are made under stress and several studies showed that stress can influence moral decision-making (Lützen et al, 2010;Starcke et al, 2011;Starcke and Brand, 2012;Youssef et al, 2012;Romero-Rivas and Rodríguez-Cuadrado, 2020). As pointed out by Francis and McNabb (2020), the COVID-19 pandemic caused radical changes in social, community, health, and political practices that could affect what is considered right or wrong and moral principles underlying decision-making processes. Moreover, public messages inspired by moral principles have increased considerably during pandemic (Everett et al, 2020;Francis and McNabb, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations